Synergizing Emotion, Common Sense, and Learning for the Development of Conscious Agents - Muhammad Adnan; Muhammad Azam; Tanveer Rafiq Tani; Sana Zafar; Umar Rafiq; Mian Mohsin Sattar (Spectrum of Engineering Sciences, 2024)
The development of conscious creatures that can mimic human cognitive capacities has long been a goal of the artificial intelligence (AI) community. The integration of emotion, common sense, and learning is still a basic difficulty, despite advancements in areas like as reasoning, problem-solving, and pattern recognition. Although these components are necessary for intelligence comparable to that of humans, they are challenging to simulate and apply. The present status of research on creating conscious entities that can integrate emotion, common sense, and adaptive learning is examined in this study. We point out important problems, suggest possible fixes, and indicate areas for further study. Keywords- Synergizing Emotion, Common Sense, Learning & Conscious Agents